ANALISIS STRATEGI PENGEMBANGAN USAHA KAIN TENUN DUSUN LENGAS DESA POTO KECAMATAN MOYO HILIR - Vivin Fitryani; Roos Nana Sucihati; Suci Purnama Sari (Pusat Riset dan Publikasi, 2020)
This study was conducted with the aim to know and analyze the strategy of developing woven cloth handicraft businesses in increasing revenue in Lengas Hamlet, Poto Village, Moyo Hilir Sub-district. Type of this study was descriptive, a study that aims to know the value of the independent variable without connecting or making comparisons with other variables. The data used in this study was qualitative data in the form of informants’ answer obtained directly from the source through interviews. The informants in this study were headman, Cooperative, Industry and Trade Office and the woven cloth business actors in Lengas Hamlet, Poto Village, Moyo Hilir Sub-district with number of informants were 20 informants. The data analysis method was done using SWOT analysis technique. The findings of this study showed that the calculation results of the IFE and EFE matrices obtained a total score that position the woven cloth handicraft business in Lengas Hamlet, Poto Village, Moyo Hilir Sub-district in the IE matrix on cell IX, which was in decrease condition. The IE matrix was adjusted with the SWOT Matrix into possible alternative development strategies, namely minimizing the use of capital, increasing promotional activities, placing businesses in strategic locations and optimizing the use of technology to increase production volume.